Collaboration Across Sectors of Adolescent Reproductive Health Education Assisted by The Semarang City Social Service - Firdha Rahma Nurbadlina; Zahroh Shaluhiyah; Antono Suryoputro (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2022)
Street children are identified as a symptom of the economic crisis and excessive urbanization. Lack of basic information and knowledge about reproductive health causes street children to be vulnerable to complex problems, one of which is risky sexual behavior. The goal of this research is to find out the cross-sectoral collaboration model in reproductive health education for street children. This research is a qualitative descriptive research with a case study research design. The research subjects were 13 main informants. The strategy used in implementing the Reproductive Health Education Services for Street Children Assisted by the Social Service is guided by the existing Street Children Reproductive Health Education Module. The instrument of data collection was in the form of guidelines for interview questions and using a tape recorder/mobile phone and stationery. Data collection techniques were carried out by in-depth interviews. Data analysis in this study used content analysis and used triangulation as a test of validity and reliability. The result of this research are street children so far have not received maximum service because socialization and education programs are usually only for school children, while for street children there is no warrant. Street children have not received more attention from the social department, health department, DP3A (Dinas Pemberdayaan Perempuan dan Perlindungan Anak). There is still a lack of focus on street children's reproductive health education because social department, health department, and DP3A are more focused on their main tasks and there is no special program for this.